The British Trade Unions and the Labour Law. The Case of the Industrial Relations Act 1971 - Ghosh, S. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
The trade unions’ reluctance to accept the reforms envisaged in the Industrial Relations Act 1971 is cited as an important example of trade unions* intransigence and arrogance and of the fact that they consider themselves to be above law. But the way the trade unions fought the Act appears to be quite in keeping with the democratic procedure and the rule of law.